IMPLICATED SUBJECTS: SOCIAL WORKERS, SETTLER COLONIALISM, AND THE QUEST FOR NON-INNOCENCE - Hoselton, Jill (Canadian Social Work Review / Revue canadienne de service social, 2024)
Drawing from Michael Rothberg’s (2019) concept of the “implicated subject,” this paper examines Canadian social work’s implication in settler colonialism from past to present through its role in Indigenous child removal from the Indian Residential Schools to the Sixties Scoop and contemporary child welfare. The “implicated subject” untangles social work from dominant discourses that position social workers as morally superior, innocent, and good, which prevents practitioners from seeing how their professional role perpetuates unintentional harm towards service-users. A practice of non-innocence is proposed, which centres the development of a critical consciousness among social workers regarding the profession’s implication in historical and contemporary harm towards Indigenous Peoples (and other marginalized populations) by way of settler colonial practices. This awareness positions practitioners as political actors with a responsibility to engage in political action dedicated towards social justice.